Clinical and molecular response to dasatinib in an adult patient with Penttinen syndrome. Issue 4 (11th December 2021) - Iznardo, Helena; Bredrup, Cecilie; Bernal, Sara; Gladkauskas, Titas; Mascaró, José‐Manuel; Roé, Esther; Baselga, Eulalia
Abstract: Penttinen type of premature aging syndrome is an autosomal‐dominant disorder that can be caused by the c.1994T>A pVal665Ala pathogenic variant in platelet‐derived growth factor receptor‐B ( PDGFRB ). Imatinib, a receptor tyrosine kinase (RTK) inhibitor, has been used in Penttinen syndrome (PS) patients with good results. A 21‐year‐old male presented shortly after birth with a prematurely aged appearance with distinctive facial features and cutaneous atrophy with hypertrophic scar‐like lesions. Generalized brachydactyly with acro‐osteolysis was observed. Flexion contractures limited his daily activities. Cognitive impairment was not present. Genetic testing found a heterozygous variant c.1994T>A pVal665Ala in exon 14 of PDGFRB . A diagnosis of PS was made and imatinib treatment was started with partial response. After lack of further improvement, in vitro molecular studies with imatinib and dasatinib showed that the Val665Ala variant had greater sensitivity to dasatinib than imatinib. This was seen examining levels of P‐PDGFRB directly and on downstream ligands P‐AKT and P‐STAT. Improved clinical response was observed after treatment with dasatinib. We report a new case of PS with clinical and molecular response to dasatinib after incomplete response to imatinib. Our work provides further molecular and clinical evidence of RTK inhibitors' efficacy in this rare disorder.